Chemistry of Stannylene‐Based Lewis Pairs: Dynamic Tin Coordination Switching Between Donor and Acceptor Character. Issue 12 (11th February 2015) - Krebs, Kilian M.; Freitag, Sarah; Schubert, Hartmut; Gerke, Birgit; Pöttgen, Rainer; Wesemann, Lars
Abstract The coordination chemistry of cyclic stannylene‐based intramolecular Lewis pairs is presented. The P→Sn adducts were treated with [Ni(COD)2] and [Pd(PCy3)2] (COD=1, 5‐cyclooctadiene, PCy3=tricyclohexylphosphine). In the isolated coordination compounds the stannylene moiety acts either as an acceptor or a donor ligand. Examples of a dynamic switch between these two coordination modes of the PSn ligand are illustrated and the structures in the solid state together with heteronuclear NMR spectroscopic findings are discussed. In the case of a Ni0 complex, 119Sn Mössbauer spectroscopy of the uncoordinated and coordinated phosphastannirane ligand is presented.